Juridical Analysis of Evidence of Crimes of Domestic Violence Against Children (Research Study at Indragiri Hilir Resort Police) - Bulan, Puti Lindung; Fadlan, Fadlan; Prasetyasari, Christiani; Nofrial, Ramon; Lubis, Irpan Husein (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
In writing this thesis, it is entitled, proving criminal acts of domestic violence against children. Proving is the process of how evidence is used. Proving is providing sufficient grounds for those examining the case in question to provide certainty about the truth of the events being presented, provide certainty to the judge regarding the truth of the events that occurred, and make clear the problem of an act. crime and find the suspect. This research uses a normative type of research supported by empirical research and also data collection techniques carried out through interviews with parties related to the research topic. Apart from that, the author also conducted library research through books and literature related to the research topic. Next, the data obtained was analyzed qualitatively and then presented descriptively. Based on the results of research and discussions in the implementation of Proof of Criminal Acts of Domestic Violence, the results of this research are in accordance with Law Number 23 of 2004 concerning the Elimination of Domestic Violence, that all forms of violence, especially domestic violence, constitute a violation of human rights. and crimes against human dignity and forms of pecuniary discrimination must be eliminated. Therefore, the state and society are obliged to carry out prevention, protection and action. The problems discussed in this thesis are the process of proving criminal acts of domestic violence against children as well as discussing the obstacles and solutions faced by investigators in carrying out proof of criminal acts of domestic violence against children. Based on the research conducted, it was concluded that the factors that cause domestic violence are economic factors, infidelity, parental experience, knowledge, environment, low legal awareness, patriarchal culture and early marriage. The obstacles are the lack of evidence, and the slow pace of reporting victims, while the solutions that have been implemented overcome the obstacles of special attention from parents, the community and law enforcement.